IMPLEMENTASI SUPERVISI AKADEMIK DAN KESEHATAN SEKOLAH PADA MASA PANDEMI COVID19 DI SDN BENER 01 TAHUN PELAJARAN 2020/2021 - Sri Ambarwati (Florea : Jurnal Biologi dan Pembelajarannya, 2021)
The Covid19 pandemic has brought significant changes to the education. The implementation of the school management function has changed in the methods and focus of activities. The implementation of the principal's leadership function includes Plan, Do, Check, Action activities in various aspects of school management. The role of school principals was very dominant in assessing the academic and health processes of schools during the Covid-19 pandemic. An alternative way that must be done to ensure quality is education supervision. Supervision is carried out by the principal, aims to record and evaluate teacher performance. The supervision that will be used in SDN Bener 01 is constructive supervision. This supervision technique provides input and direction to the teacher. This research was conducted in January-March 2021. The research site was SDN Bener 01, Saradan District, Madiun Regency with the target of 8 teachers. The result of academic supervision is that in general there has been an increase in teachers' academics in learning during the Covid19 pandemic. The percentage of teachers with the minimum criteria is good as much as 100%. Several aspects, the teacher got very good results. The results showed that the facilities and infrastructure as well as the implementation of health protocols at SDN Bener 01 were categorized as Very Good.